RELATIONSHIP OF EMPLOYMENT OPPORTUNITIES WITH EDUCATION NEEDS IN ARISAN MUSI VILLAGE, MUARA BELIDA DISTRICT - Kms. Rahmat Abdul Ghofur; Thoriq Habsyi; Dinda Cici Aulia; Rizki Anantha Emdardi; Maya Panorama (Penerbit Lafadz Jaya, 2022)
Educational demands driven by educational growth have grown the economy of the people of Arisan Musi Village, Muara Belida District, Muara Enim Regency by increasing job opportunities. The allocation of knowledgeable human resources is the beginning of economic growth. education in Arisan Musi Village is quite good compared to previous years. The descriptive analysis aims to explain the development of the education level of the people of Arisan Musi Village, Muara Belida Regency, South Sumatra Province. Education can improve the quality of human resources which in turn can help foster public understanding of development. Therefore, to have the ability to participate in society, it is necessary to increase human resources through education. There are various aspects that can improve the quality of human resources such as health, education, and so on. With many people starting to migrate and work in better jobs than depending on plantations in Arisan Musi Village. The quality of human resources is the foundation for successful development. So that internal and external factors that affect the quality of human resources become better, and village growth becomes better. Good education can also produce good human resources. These quality human resources can increase productivity at work so that the opportunity to work is higher and the economic situation is getting better in the village of Arisan Musi. Because if the quality of human resources is good, it can support the development process of an area to develop into a growth center.